Mechanistic insights into Calotropis procera extract and green-silver nanoparticles as therapeutic agents in murine schistosomiasis: Targeting BAX/Bcl-2 and oxidative stress (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study aims to make a comparative evaluation of the therapeutic efficacies of the Calotropis extract (CpE) and green silver nanoparticles (GSNPs) compared to praziquantel (PZQ) in treating mice infected with schistosomiasis, with a comprehensive assessment of host physiological responses. Materials and Methods: The CpE-fabricated silver nanoparticles were characterized (UV-vis spectroscopy, transmission electron microscopy, and Fourier transform infrared). Five experimental groups were conducted: uninfected, infected untreated, PZQ-, CpE-, and GSNP-treated. The parasitological, biochemical, histopathological, and ultrastructural approaches were employed in evaluating each treatment protocol. Results: It was found that the reduction of the worm burden and oogram count was significantly enhanced by both CpE and GSNPs, yet PZQ showed better antiparasitic effects. The antioxidant activity of GSNPs was more efficient, and they significantly restored hepatic (glutathione) as well as reduced (malondialdehyde) and (nitric oxide) levels. In addition, both CpE and GSNPs regulated apoptotic markers by inhibiting Bcl2-cell-associated X protein and enhancing B-cell lymphoma protein 2 expression, thereby inhibiting hepatocyte apoptosis. Histopathological examination revealed a reduction in granuloma size and hepatic fibrosis, along with an improved hepatoprotective potential of GSNPs. Biochemical analysis revealed increased activity of liver enzymes (alanine transaminase, aspartate transaminase, and gamma-glutamyl transferase) as well as markers of renal function (urea and creatinine), indicating they also had a systemic protective role. All treatments resulted in some ultrastructural alterations in worms. Conclusion: The normalized parasitological and physiological parameters were utilized in developing a novel mathematical framework that facilitates more objective assessments for treatment protocols. Although PZQ showed the highest efficacy against the parasite (total efficacy score: 71.8), the plant extract showed the highest efficacy in anti-fibrotic and anti-apoptotic properties (total efficacy score: 61.6). However, GSNPs showed balanced therapeutic benefits (total efficacy score: 51.1). This study indicated that comparison based on both the host physiological parameters and those of the parasite is more comprehensive for optimal anti-schistosomal treatment selection. This study also confirmed that treatments derived from plant sources may have complementary benefits over traditional chemotherapy through metabolic pathways involved in the host protective responses.J. Adv. Vet. Anim. Res., 12(4): 1314–1332, December 2025http://doi.org/10.5455/javar.2025.l992